Photoionization and photo-induced processes in mass spectrometry : fundamentals and applications - Zimmermann, Ralf; Hanley, Luke (Wiley-VCH, 2021)
Drawing on the expertise of the leading academic and industrial research groups involved in the development of photoionization methods for mass spectrometry, this reference for analytical scientists covers both the theory and current applications of photo-induced ionization processes. It places widely used techniques such as MALDI side by side with more specialist approaches such as REMPI and RIMS, and discusses leading edge developments in ultrashort laser pulse desorption, to give readers a complete picture of the state of the technology. This book starts with a complete overview of the fundamentals of the technique, covering the basics of the gas phase ionization as well as those of laser desorption and ablation, pulse photoionization, and single particle ionization. Numerous application examples from different analytical fields are described that showcase the power and the wide scope of photo ionization in mass spectrometry.
Keywords: Mass spectrometry -- Technique.; elektronické knihy; electronic books